United States Federal Mandatory Minimum Statutes Study, 1989-1990 ([Verlag nicht ermittelbar], 1993)
In response to a Congressional directive, the United States Sentencing Commission completed this study of federal mandatory minimum statutes with an emphasis on the presence and/or applicability of statutes prior to conviction and sentencing. To collect this type of detailed information, it was necessary to examine actual offense behavior. To that end, the Commission selected for detailed review a 12.5-percent random sample of its FY90 database of 29,011 cases, focusing on controlled substance offenses and firearms violations. The screening process yielded 1,165 cases. For these defendants, information was recorded on real offense components, indictment history, mode of conviction, and convicted charges, as well as sentence imposed, plea agreements, stipulations, and guideline factors. This information allows for a procedural tracking of cases and the application of mandatory minimum provisions at various stages of the criminal justice process.